Characterization and radiation shielding properties of Philippine natural bentonite and zeolite - Gili, Mon Bryan Z.; Hila, Frederick C. (Philippine journal of science)
"In this paper, the investigation of the structural and radiation shielding characteristics of natural bentonite and zeolite was presented. XRD (X-ray diffraction) and SEM (scanning electron microscopy) were used to examine the structural properties and morphologies of the minerals. The Electron-Photon Interaction Cross Sections 2017 (EPICS2017) library through EpiXS software was used to obtain the photon shielding properties - including mass attenuation coeffiecients, mean free paths, half-value and tenth value layers" - title page.